ANALISIS TENTANG EKSEPSI KEWENANGAN ABSOLUT YANG DITOLAK OLEH MAJELIS HAKIM (PUTUSAN NO 420/PDT.G/2020/PN JKT.SEL) : Analysis Of The Exception Of Absolute Authority Rejected By The Council Of Judges (Ruling No 420/Pdt.G/2020/Pn Jkt.Sel) - Bhakti Arssywahid; Muriani (Reformasi Hukum Trisakti, 2024)
Resolving civil disputes through the courts is still an option for many legal subjects, where the District Court Panel of Judges will make the decision. However, in Decision No. 420/Pdt.g/2020/Pn Jkt.Sel, the District Court Panel of Judges rejected the defendant's exception or denial regarding the exception of absolute competence. The formulation of the problem in this research is whether the rejection of the exception regarding Absolute Competence from the Defendant is in accordance with the relevant laws and regulations and what legal remedies the Defendant can take. The type of research used is normative juridical using secondary data. Research Results The rejection of absolute competence by the Panel of Judges at the South Jakarta District Court is in accordance with Article 1365 of the Civil Code, Article 50 of Law no. 2 of 1986 concerning General Courts, and legal remedies for the Defendants if they feel dissatisfied with the rejection of this exception regarding absolute competence in accordance with Article 9 paragraph (1) of Law Number 20 In 1947, by filing a legal appeal and Article 43 paragraph (1) of Law Number 14 of 1985, the defendant can file cassation legal remedy, and if not satisfied, can file  judicial review.